Analytical investigation of solar air heater with jet impingement using energy and exergy analysis. (February 2018) - Matheswaran, M.M.; Arjunan, T.V.; Somasundaram, D.
Highlights: An analytical model evaluates the thermo hydraulic and exergy efficiency of proposed SPDDJPSAH. The effect of jet plate design parameters and their influences are analyzed. Optimal parameters for maximum exergy efficiency and design plots are suggested. Correlation shows that the Jet diameter ratio has stronger effect on exergy efficiency. Abstract: In this present work an exergy efficiency of the single pass double duct jet plate solar air heater (SPDDJPSAH) is analytically investigated. The analysis is carried out for different mass flow rate m = 0.002–0.023 kg/s, stream wise pitch ratio X / Dh = 0.435–1.739, span wise pitch ratio Y / Dh = 0.435–0.869 and jet diameter ratio Dj /Dh = 0.043–0.109. The overall performance of solar air heaters is effectively evaluated by the exergy analysis by considering both the useful energy gain and subsequent pumping power requirement. Results show that SPDDJPSAH has been enhancing the effective efficiency by 21.2% and exergy efficiency by 22.4% when compared with Single Pass Single Duct Jet Plate Solar Air Heater (SPSDJPSAH). The effects of mass flow rate and jet plate design parameters on the exergy efficiency have been presented. The optimized values of stream wise pitch ratio X / Dh = 1.739, span wise pitch ratio Y / Dh = 0.869 and jet diameter ratio Dj / Dh = 0.065 are identified at the mass flow rate of 0.0035 kg/s and yields the maximum exergy efficiency of 4.36%. Design plots are also prepared in order to identify the optimum values of jet plate design parameters to achieve the desired temperature rise. Using the analytical results, the correlations have been developed for predicting the exergy efficiency in terms of Reynolds number and jet plate design variables.